Most relevant neuropathic pain treatment and Chronic Low Back Pain Management guidelines: A Change Pain Latin America advisory panel consensus (2018)
Objective. Chronic pain conditions profoundly affect the daily living of a significant number of people and are a major economic and social burden, particularly in developing countries. The Change Pain Latin America (CPLA) advisory panel aimed to identify the most appropriate guidelines for the treatment of neuropathic pain (NP) and chronic low back pain (CLBP) for use across Latin America. Methods. Published systematic reviews or practice guidelines were identified by a systematic search of PubMed, the Guidelines Clearinghouse, and Google. Articles were screened by an independent reviewer, and potential candidate guidelines were selected for more in-depth review. A shortlist of suitable guidelines was selected and critically evaluated by the CPLA advisory panel. Results. Searches identified 674 and 604 guideline articles for NP and CLBP, respectively. Of these, 14 guidelines were shortlisted for consensus consideration, with the following final selections made: • 'Recommendations for the pharmacological management of neuropathic pain from the Neuropathic Pain Special Interest Group in 2015-pharmacotherapy for neuropathic pain in adults: A systematic review and meta-analysis.' • 'Diagnosis and treatment of low back pain: A joint clinical practice guideline from the American College of Physicians and the American Pain Society' (2007). Conclusions. The selected guidelines were endorsed by all members of the CPLA advisory board as the best fit for use across Latin America. In addition, regional considerations were discussed and recorded. We have included this expert local insight and advice to enhance the implementation of each guideline across all Latin American countries. © 2017 American Academy of Pain Medicine.